Dzietność małżeństw według wybranych cech społeczno-ekonomicznych w Republice Federalnej Niemiec - Schwartz, Karl (Wydział Prawa i Administracji UAM, 1981)
A review of birth development in Germany within the last hundred years leads to determination of the present level of the number of children as very low, hence importance of some selected socio-economic features for a number of children possessed by married couples has been examined. It has been stated that the family number of children grows smoothly along with husbands' incomes. Such an observation has been made especially for families in which the woman does not work professionally. Married couples, in which women work professionally, possess significantly less children than others. Particularly, absence of children has been stated in the marriages, in which women earn relatively much money. Irrespective of women's paid work and of income level, the number of children is determined by standards of particular classes of society. The highest number of children occurs in self-dependent farms, then in marriages of workers, officials, and at the end — always with a very low number of children — marriages of employees. Decrease in the share of marriages of workers and of self-dependent farms, as well as the growth of the share of employees' marriages within the past 50 years, have influenced slightly the average number of children of all married couples. There is a justification, in spite of many reservations, for continuation of research on fertility differentiation when data from official statistics used.
Number of Children in Families by Chosen Socio-Economic Features in the Federal Republic of Germany